The Spotted Iris: Unveiling a Case of Bilateral Iris Mammillations in a Type 1 Diabetic Adolescent - Swaranjali Gore; Nagyang Dani; (Col.) OK Radhakrishnan; Harshita Kashyap; Naina Chaturvedi (Journal of Clinical and Diagnostic Research)
Bilateral iris mammillations are an exceedingly rare ocular anomaly characterised by small, papilliform nodules that cover part or the entire surface of the iris. Although often associated with systemic conditions such as Neurofibromatosis (NF), oculodermal melanocytosis, or phakomatosis pigmentovascularis, isolated bilateral cases are infrequently reported. This report describes a case of a 14-year-old male who presented for a routine dilated fundus examination at a tertiary care centre. The patient, a known case of Type 1 Diabetes Mellitus (DM) for 11 years, was maintained on subcutaneous human Actrapid insulin. He reported no ocular complaints. Examination revealed a best-corrected visual acuity of 6/6 in both eyes with intact colour vision. Slit lamp examination identified multiple, diffuse, small, round, nodular elevations over the surface of both irides without evidence of iris neovascularisation. Gonioscopy revealed open angles without trabecular hyperpigmentation. Posterior segment evaluation, including Optical Coherence Tomography (OCT) and B-scan ultrasonography, was unremarkable. Ultrasound biomicroscopy confirmed the absence of ciliary body involvement. Systemic examination showed no evidence of NF, oculodermal melanocytosis, or phakomatosis pigmentovascularis. Genetic testing for NF type 1 returned negative. The presence of isolated bilateral iris mammillations without systemic association is exceedingly rare. This case adds valuable data to the limited literature on such presentations and highlights the importance of thorough ocular and systemic evaluation to differentiate these nodules from other ocular anomalies. Continued surveillance and long-term follow-up are crucial, given the potential but rare association with secondary glaucoma and ocular malignancy.